Cu modified graphite phase carbon nitride photocatalyst, preparation method and application thereof

Through the preparation of Cu-modified graphite phase carbon nitride photocatalyst, the problem of low light utilization rate of graphite phase carbon nitride photocatalyst and low separation efficiency of photogenerated electron-hole pairs when degrading antibiotics is solved, and efficient antibiotic removal effect is achieved.

CN119608206APending Publication Date: 2025-03-14UNIV OF JINAN +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411672603.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

When graphite phase carbon nitride photocatalysts use photocatalytic technology to degrade antibiotics, the sun's light utilization rate is low and the photogenerated electron-hole pair separation efficiency is low, resulting in low quantum efficiency, limiting its practical application in the field of antibiotic treatment in the environment.

Method used

Graphite-phase carbon nitride two-dimensional nanosheets were synthesized by heat-condensing polymerization, and mixed and calcined with copper ethylenediaminetetraacetate (Cu-EDTA) to construct Cu-modified graphite-phase carbon nitride photocatalyst (Cu-CN) to improve its photocatalytic efficiency.

Benefits of technology

The introduction of Cu-CN photocatalysts broadened the photoresponse range, inhibited the recombination of photogenerated electron-hole pairs, significantly improved its photocatalytic activity, and the removal rate of antibiotics can be as high as more than 98% within 30 minutes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608206A_ABST
    Figure CN119608206A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of environmental pollution treatment, and particularly relates to a Cu modified graphite phase carbon nitride photocatalyst as well as a preparation method and application thereof. The preparation method specifically comprises the following steps: preparing graphite phase carbon nitride nanosheets (g-C3N4, CN) through a thermal polycondensation method, mixing the CN two-dimensional nanosheets and Cu-EDTA, drying by distillation, and calcining to obtain the Cu-CN photocatalyst. The photocatalyst disclosed by the invention has the advantages of strong light response capability, high photon-generated carrier separation efficiency and the like. Experiments prove that the Cu-CN photocatalyst has a good visible light photocatalytic removal effect on tetracycline hydrochloride, and the removal rate of 40mg / L tetracycline hydrochloride within 30min is up to 98% or above. The invention has the advantages of economy, environmental protection, simple preparation method and suitability for industrial large-scale production, and has certain economic and social effects in the aspect of antibiotic pollution treatment in the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmental pollution control, and specifically relates to a Cu-modified graphite phase carbon nitride photocatalyst, a preparation method and application thereof. Background Art

[0002] Antibiotics are a type of medicinal substance used to treat and prevent bacterial infections. They are widely used in medicine, animal husbandry, and aquaculture. Studies have shown that between 2000 and 2008, the use of antibiotics increased by 46%; by 2030, global antibiotic use will reach 40 billion limited daily doses. While these antibiotics bring convenience to humans, they also bring an urgent environmental problem to be solved: antibiotic residues. After antibiotics enter the human or animal body, only about 30% are absorbed. Most of them enter the environment in the form of prototypes or metabolites with excrement. Antibiotics have been detected in water bodies such as oceans, rivers, lakes, and groundwater in many parts of the world. They not only change the composition and activity of microorganisms and the ecological structure of microbial communities, but also promote the formation of drug-resistant infections, causing harm to the ecological environment and human health.

[0003] To solve this problem, people have designed a variety of cost-effective technologies to remove antibiotics from the environment, including microbial degradation, activated carbon adsorption, membrane separation, chemical oxidation, electrocoagulation, etc. However, these methods are not suitable for large-scale use due to their high operating costs, large energy requirements, many by-products, and low treatment efficiency. Therefore, there is an urgent need to develop efficient and low-environmental-impact antibiotic degradation methods. Photocatalytic technology has the advantages of being environmentally friendly, low cost, easy to operate, high efficiency, and no secondary pollution, and has gradually become an efficient antibiotic treatment mode. Photocatalytic technology is a semiconductor material that converts solar energy into chemical energy under the irradiation of sunlight of a certain wavelength, and converts antibiotic pollutants in water into low-toxic small molecules through redox reactions with antibiotics adsorbed on its surface, and even completely decomposes antibiotics to form non-toxic CO2 and H2O, thereby achieving complete removal of antibiotics from the environment.

[0004] Graphitic carbon nitride (g-C3N4, CN) is considered to be an important photocatalyst because of its low cost, non-toxicity, stability, unique electronic band structure, and excellent physical and chemical stability. However, there are two main problems in the application of CN materials in the research on the degradation of antibiotics using photocatalytic technology: first, the utilization rate of sunlight is relatively low, and it can only absorb the visible light part of sunlight, and cannot effectively utilize the light energy in different wavelength regions of the solar spectrum; second, the low separation efficiency of photogenerated electron-hole pairs in CN materials leads to low quantum efficiency, which limits its practical application in the field of antibiotic treatment in the environment. Therefore, it is necessary to modify or modify a single CN material to improve its photocatalytic efficiency. Summary of the invention

[0005] In view of this, the present invention proposes a method for preparing a Cu-modified graphite phase carbon nitride photocatalyst (Cu-CN), wherein the method synthesizes CN two-dimensional nanosheets by a thermal shrinkage polymerization method, mixes and calcines the CN two-dimensional nanosheets and copper ethylenediaminetetraacetate (Cu-EDTA), thereby constructing a Cu-CN photocatalyst, and the catalyst is applied to the photocatalytic degradation of antibiotics in water.

[0006] The present invention adopts the following technical solutions:

[0007] A method for preparing a Cu-modified graphite-phase carbon nitride photocatalyst, the method comprising the following steps:

[0008] Step 1, weighing an appropriate amount of urea and putting it into a ceramic crucible with a cover, calcining it in air, and cooling it to room temperature after calcining to obtain graphite phase carbon nitride (g-C3N4, CN);

[0009] Step 2, mixing the CN obtained in step 1 with copper ethylenediaminetetraacetate (Cu-EDTA) and methanol, ultrasonicating, stirring, and evaporating in a water bath to obtain a Cu-EDTA / CN mixture; the molar ratio of Cu-EDTA to CN is 0.1 to 2:100;

[0010] Step 3, placing the Cu-EDTA / CN mixture obtained in step 2 in a covered ceramic crucible and calcining it under the protection of an inert gas, and naturally cooling it to room temperature after the calcination to obtain a Cu-modified graphite phase carbon nitride photocatalyst (Cu-CN).

[0011] Transmission electron microscopy (TEM) confirmed that Cu atoms were uniformly dispersed on the CN nanosheets.

[0012] Preferably, in step 1, the calcination temperature is 550±50°C, the calcination time is 3-6h, and the heating rate is 4-7°C / min.

[0013] Preferably, in step 2, the usage ratio of CN to methanol is 0.5-3 mg / mL.

[0014] Preferably, in step 2, the ultrasonic time is 10-50 min, the water bath temperature is 55-85° C., and the water bath time is 6-9 h.

[0015] Preferably, in step 2, the molar ratio of Cu-EDTA to CN is 0.2-2:100, more preferably 0.5-1.0:100, and most preferably 0.5:100.

[0016] Preferably, in step 3, the calcination temperature is 450±50°C, the calcination time is 0.5-2h, the heating rate is 2-4°C / min, and nitrogen is the best protective gas.

[0017] A Cu-modified graphite-phase carbon nitride photocatalyst prepared by the preparation method of the invention.

[0018] An application of the Cu-modified graphite phase carbon nitride photocatalyst of the present invention in the photocatalytic degradation of antibiotics in water. Preferably, the application is specifically: under light, the antibiotics and the Cu-CN photocatalyst are mixed in a solvent system (preferably water) to achieve the removal effect of the antibiotics. The concentration of the Cu-CN photocatalyst is 0.5-1.5 mg / mL, and the concentration of the antibiotics is 20-60 mg / L. The lighting conditions can be natural light, preferably a xenon lamp, and more preferably a 300W±100W xenon lamp.

[0019] The application test was carried out in a Beijing Zhongjiao Jinyuan CEL-LAX500 photochemical reactor using a 300 W xenon lamp with a 420 nm cutoff filter as the light source and tetracycline hydrochloride (TCH) as the antibiotic model molecule. The concentration of TCH in the solution was determined by a high performance liquid chromatograph (Agilent, 1260infinity II).

[0020] Function and Effect of the Invention

[0021] In the present invention, CN two-dimensional nanosheets with large specific surface area and special electronic structure are used as the base material, and Cu-CN photocatalysts are prepared by compounding with Cu-EDTA molecules. The introduction of Cu atoms can broaden the light response range of CN nanosheets, inhibit the recombination of photogenerated electron-hole pairs, and effectively improve their photocatalytic activity.

[0022] In addition, in view of the serious antibiotic pollution in the environment, the present invention proposes to use metal Cu atoms to modify graphite carbonized nitrogen to prepare a photocatalyst to degrade antibiotics and achieve the removal of antibiotics in water. When the molar ratio of Cu-EDTA to CN nanosheets is 0.5:100, the efficiency of Cu-CN photocatalyst in photocatalytic removal of antibiotics is the highest, and the removal rate of antibiotics can reach more than 98% within 30 minutes of visible light illumination.

[0023] The preparation method of a Cu-modified graphite-phase carbon nitride photocatalyst provided by the invention has the characteristics of simplicity, economy, stability and the like, and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a process flow chart of the preparation of the Cu-CN photocatalyst in Examples 1-3 of the present invention;

[0025] Figure 2 It is the XRD diffraction pattern of the base CN in Comparative Example 1 and the Cu-CN photocatalyst in Examples 1-3 described in the present invention;

[0026] Figure 3 TEM spectra and mapping diagrams of the basic CN in Comparative Example 1 and the Cu-CN-0.5 photocatalyst in Example 2 of the present invention, wherein (a) is the TEM image of the basic CN in Comparative Example 1; (b) is the TEM image of the Cu-CN-0.5 photocatalyst obtained in Example 2; (c) is the distribution diagram of C, N, and Cu elements in a selected area of ​​the Cu-CN-0.5 photocatalyst obtained in Example 2;

[0027] Figure 4 It is the UV-vis spectrum of the basic CN in Comparative Example 1 and the Cu-CN photocatalyst in Examples 1-3 of the present invention, and the illustration is the sample picture of the basic CN in Comparative Example 1 and the Cu-CN photocatalyst in Examples 1-3;

[0028] Figure 5 It is the IT and EIS spectra of the basic CN in Comparative Example 1 and the Cu-CN-0.5 photocatalyst in Example 2 of the present invention;

[0029] Figure 6 The performance graph (a) of the photocatalytic removal of antibiotics in water by the Cu-CN photocatalyst in Comparative Examples 1-3 and Example 3 of the present invention, and the performance graph (b) of the photocatalytic removal of antibiotics in water by the Cu-CN photocatalyst in Example 1-6;

[0030] Figure 7 This is a cycle performance diagram of the photocatalytic removal of antibiotics in water by the Cu-CN-0.5 photocatalyst in Example 3 of the present invention. DETAILED DESCRIPTION

[0031] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0032] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0033] The present invention is now further described in conjunction with specific examples. The following examples are only for explaining the present invention, but do not constitute a limitation of the present invention. The test samples and test processes used in the following examples include the following (if the specific experimental conditions are not indicated in the examples, they are usually in accordance with conventional conditions or the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, if not otherwise specified, can all be obtained from commercial channels).

[0034] The core technology of the present invention is a method for preparing a Cu-modified graphite-phase carbon nitride photocatalyst. The process flow chart is as follows: Figure 1 As shown, the method comprises the following steps:

[0035] Step 1, weigh an appropriate amount of urea and put it into a ceramic crucible with a cover, calcine it in air, and cool it to room temperature after calcination to obtain CN nanosheets.

[0036] Step 2, mixing CN obtained in step 1 with Cu-EDTA and methanol, ultrasonicating, stirring, and evaporating in a water bath to obtain a Cu-EDTA / CN mixture; the molar ratio of Cu-EDTA to CN is 0.1 to 2:100.

[0037] Step 3, placing the Cu-EDTA / CN mixture obtained in step 2 in a ceramic crucible with a lid, calcining under a nitrogen atmosphere, and naturally cooling to room temperature after calcination to obtain a Cu-modified graphite phase carbon nitride photocatalyst (Cu-CN).

[0038] Comparative Example 1

[0039] 5 g of urea was placed in a ceramic crucible with a lid, and calcined in a muffle furnace at 550° C. for 4 h at a heating rate of 5° C. / min to obtain a basic graphite-phase carbon nitride photocatalyst (CN).

[0040] According to the test method for photocatalytic degradation of antibiotics described in the application example, the CN photocatalyst prepared in this comparative example was subjected to photocatalytic degradation of antibiotics, and the removal rate within 30 minutes of visible light illumination could reach 14%.

[0041] Comparative Example 2

[0042] A method for preparing a Cu-modified graphite-phase carbon nitride photocatalyst, comprising the following specific steps:

[0043] Step 1, weigh 5g of melamine sponge and put it into a ceramic crucible with a lid, put the crucible into a muffle furnace and calcine it at a temperature of 550°C, a calcination time of 4h, and a heating rate of 5°C / min to obtain basic graphite phase carbon nitride (CN-m).

[0044] Step 2, place 0.0129 g of Cu-EDTA, 0.6000 g of CN-m obtained in step 1, and 70 mL of methanol in a 100 mL beaker, mix them by ultrasonication for 30 min, then keep them in a 70°C water bath for 6 h, evaporate the solvent, and the resulting solid is a Cu-EDTA / CN-m mixture.

[0045] Step 3: The Cu-EDTA / CN-m mixture obtained in step 2 is placed in a magnetic boat and calcined in a tube furnace at 450°C for 1 hour at a heating rate of 2.5°C / min with nitrogen as the protective gas to obtain a Cu-modified graphite phase carbon nitride photocatalyst (Cu-CN-0.5-m).

[0046] In the Cu-CN-0.5-m photocatalyst obtained above, the molar ratio of Cu-EDTA to CN-m is 0.5:100.

[0047] According to the test method for photocatalytic degradation of antibiotics described in the application example, the Cu-CN-0.5-m photocatalyst prepared in this comparative example was subjected to photocatalytic degradation of antibiotics, and the removal rate within 30 minutes of visible light illumination could reach 31%.

[0048] Comparative Example 3

[0049] A method for preparing a Cu-modified graphite-phase carbon nitride photocatalyst, comprising the following specific steps:

[0050] Step 1, weigh 5g of urea and put it into a ceramic crucible with a lid, put the crucible into a muffle furnace and calcine it at a temperature of 550°C, a calcination time of 4h, and a heating rate of 5°C / min to obtain basic graphite phase carbon nitride (CN).

[0051] Step 2: Place 0.0129 g of Cu-EDTA, 0.6000 g of CN obtained in step 1, and 70 mL of methanol in a 100 mL beaker, mix by ultrasonication for 30 min, and then keep in a 70° C. water bath for 6 h. Evaporate the solvent to obtain a solid Cu-EDTA / CN mixture.

[0052] Step 3: The Cu-EDTA / CN mixture obtained in step 2 is placed in a ceramic crucible with a lid, and calcined at 450°C for 1 h in a muffle furnace at a heating rate of 2.5°C / min. After the calcination, it is naturally cooled to room temperature to obtain a Cu-modified graphite phase carbon nitride photocatalyst (Cu-CN-0.5-A).

[0053] In the Cu-CN-0.5-A photocatalyst obtained above, the molar ratio of Cu-EDTA to CN is 0.5:100.

[0054] According to the test method for photocatalytic degradation of antibiotics described in the application example, the Cu-CN-0.5-A photocatalyst prepared in this comparative example was subjected to photocatalytic degradation of antibiotics, and the removal rate within 30 minutes of visible light illumination could reach 34%.

[0055] Example 1

[0056] A method for preparing a Cu-modified graphite-phase carbon nitride photocatalyst, comprising the following specific steps:

[0057] Step 1, weigh 5g of urea and put it into a ceramic crucible with a lid, put the crucible into a muffle furnace and calcine it at a temperature of 550°C, a calcination time of 4h, and a heating rate of 5°C / min to obtain basic graphite phase carbon nitride (CN).

[0058] Step 2, place 0.0052 g of Cu-EDTA, 0.6000 g of CN obtained in step 1, and 70 mL of methanol in a 100 mL beaker, mix them by ultrasonication for 30 min, then keep them in a 70° C. water bath for 6 h, evaporate the solvent, and the resulting solid is a Cu-EDTA / CN mixture.

[0059] Step 3: The Cu-EDTA / CN mixture obtained in step 2 is placed in a magnetic boat and calcined in a tube furnace at 450°C for 1 hour at a heating rate of 2.5°C / min with nitrogen as the protective gas to obtain a Cu-modified graphite phase carbon nitride photocatalyst (Cu-CN-0.2).

[0060] In the Cu-CN-0.2 photocatalyst obtained above, the molar ratio of Cu-EDTA to CN is 0.2:100.

[0061] According to the test method for photocatalytic degradation of antibiotics described in the application example, the Cu-CN-0.2 photocatalyst prepared in this example was subjected to photocatalytic degradation of antibiotics, and the removal rate within 30 minutes of visible light illumination could reach 56%.

[0062] Example 2

[0063] A method for preparing a Cu-modified graphite-phase carbon nitride photocatalyst, wherein the specific steps are the same as those of Example 1, except that the molar ratio of Cu-EDTA to CN is 0.3:100.

[0064] According to the test method for photocatalytic degradation of antibiotics described in the application example, the Cu-CN photocatalyst prepared in this embodiment was subjected to photocatalytic degradation of antibiotics, and the removal rate within 30 minutes of visible light irradiation could reach 52%.

[0065] Example 3

[0066] A method for preparing a Cu-modified graphite-phase carbon nitride photocatalyst, comprising the following specific steps:

[0067] Step 1, weigh 5g of urea and put it into a ceramic crucible with a lid, put the crucible into a muffle furnace and calcine it at a temperature of 550°C, a calcination time of 4h, and a heating rate of 5°C / min to obtain basic graphite phase carbon nitride (CN).

[0068] Step 2: Place 0.0129 g of Cu-EDTA, 0.6000 g of CN obtained in step 1, and 70 mL of methanol in a 100 mL beaker, mix by ultrasonication for 30 min, and then keep in a 70° C. water bath for 6 h. Evaporate the solvent to obtain a solid Cu-EDTA / CN mixture.

[0069] Step 3: The Cu-EDTA / CN mixture obtained in step 2 is placed in a magnetic boat and calcined in a tube furnace at 450°C for 1 hour at a heating rate of 2.5°C / min with nitrogen as the protective gas to obtain a Cu-modified graphite phase carbon nitride photocatalyst (Cu-CN-0.5).

[0070] In the Cu-CN-0.5 photocatalyst obtained above, the molar ratio of Cu-EDTA to CN is 0.5:100.

[0071] According to the test method for photocatalytic degradation of antibiotics described in the application example, the Cu-CN-0.5 photocatalyst prepared in this example was subjected to photocatalytic degradation of antibiotics, and the removal rate within 30 minutes of visible light irradiation could reach 98%.

[0072] Example 4

[0073] A method for preparing a Cu-modified graphite-phase carbon nitride photocatalyst, wherein the specific steps are the same as those of Example 1, except that the molar ratio of Cu-EDTA to CN is 1.0:100.

[0074] According to the test method for photocatalytic degradation of antibiotics described in the application example, the Cu-CN photocatalyst prepared in this embodiment was subjected to photocatalytic degradation of antibiotics, and the removal rate within 30 minutes of visible light illumination could reach 90%.

[0075] Example 5

[0076] A method for preparing a Cu-modified graphite-phase carbon nitride photocatalyst, comprising the following specific steps:

[0077] Step 1, weigh 5g of urea and put it into a ceramic crucible with a lid, put the crucible into a muffle furnace and calcine it at a temperature of 550°C, a calcination time of 4h, and a heating rate of 5°C / min to obtain basic graphite phase carbon nitride (CN).

[0078] Step 2, place 0.0387 g of Cu-EDTA, 0.6000 g of CN obtained in step 1, and 70 mL of methanol in a 100 mL beaker, mix them by ultrasonication for 30 min, then keep them in a 70° C. water bath for 6 h, evaporate the solvent, and the resulting solid is a Cu-EDTA / CN mixture.

[0079] Step 3: The Cu-EDTA / CN mixture obtained in step 2 is placed in a magnetic boat and calcined in a tube furnace at 450°C for 1 hour at a heating rate of 2.5°C / min with nitrogen as the protective gas to obtain a Cu-modified graphite phase carbon nitride photocatalyst (Cu-CN-1.5).

[0080] In the Cu-CN-1.5 photocatalyst obtained above, the molar ratio of Cu-EDTA to CN is 1.5:100.

[0081] According to the test method for photocatalytic degradation of antibiotics described in the application example, the Cu-CN-1.5 photocatalyst prepared in this example was subjected to photocatalytic degradation of antibiotics, and the removal rate within 30 minutes of visible light irradiation could reach 83%.

[0082] Example 6

[0083] A method for preparing a Cu-modified graphite-phase carbon nitride photocatalyst, wherein the specific steps are the same as those of Example 1, except that the molar ratio of Cu-EDTA to CN is 2.0:100.

[0084] According to the test method for photocatalytic degradation of antibiotics described in the application example, the Cu-CN photocatalyst prepared in this embodiment was subjected to photocatalytic degradation of antibiotics, and the removal rate within 30 minutes of visible light illumination could reach 86%.

[0085] According to the above test results, when the molar ratio of Cu-EDTA to CN is 0.5:100, the photocatalytic degradation of antibiotics is better, and the optimal molar ratio is 0.5:100.

[0086] Characterization of the basic CN prepared in the above comparative example and the Cu-CN photocatalysts prepared in each example:

[0087] XRD diffraction pattern: Figure 2As shown, the basic CN obtained in Comparative Example 1 has two obvious diffraction peaks at 13° and 27°, which correspond to the triazine structural unit (100) in the lattice plane parallel to the c-axis and the (002) plane caused by the periodic superposition of each layer. Relative to the basic CN, the Cu-CN photocatalysts obtained in each embodiment have the same peak shape, but with the increase of Cu content, the diffraction peak intensity around 27° gradually increases, indicating that the introduction of Cu enhances the crystallinity of CN crystals. In addition, no obvious Cu diffraction peak was observed in XRD, which is due to the small amount of Cu introduced, more uniform dispersion and lower crystallinity.

[0088] TEM and mapping diagram: Figure 3 As shown, the basic CN obtained in Comparative Example 1 is in the form of nanosheets ( Figure 3 (a) The morphology of the Cu-CN photocatalyst modified by Cu still maintains the nanosheet structure of the basic CN ( Figure 3 (b)). Figure 3 (c) is the distribution diagram of C, N, and Cu elements in the selected area, which shows that the C and N elements in the catalyst are evenly distributed, and Cu is relatively evenly dispersed on the CN nanosheets.

[0089] UV-vis spectrum: Figure 4 As shown, the absorption band edge of the basic CN obtained in Comparative Example 1 is about 450nm; after the introduction of Cu, the absorption band of the Cu-CN photocatalyst does not change significantly compared with the basic CN, but the absorbance in the visible light region is significantly enhanced. This phenomenon shows that the ability of the Cu-CN photocatalyst to capture visible light has been significantly improved. Under the irradiation of visible light, the total number of conduction band electrons and the total number of valence band holes of the material can be greatly increased, which is of great benefit to the improvement of the catalyst's ability to photocatalytically degrade antibiotics.

[0090] Electrochemical performance diagram: Figure 5 (a) shows the transient photocurrent response curves of the basic CN obtained in Comparative Example 1 and the Cu-CN-0.5 obtained in Example 2, and tests the samples for several cycles of response to light irradiation and no light irradiation. Compared with the basic CN, the Cu-CN-0.5 photocatalyst clearly shows a stronger photocurrent response signal at the moment of turning on the light, indicating that it has a stronger ability to separate and migrate photogenerated charges; from the impedance curve in 5(b), it can be seen that compared with the basic CN, the Cu-CN-0.5 photocatalyst has a smaller Nyquist arc radius, indicating that it has a lower photogenerated charge transfer resistance, which is conducive to the rapid transfer and separation of photogenerated carriers, and is conducive to improving the photocatalytic performance of the catalyst.

[0091] Application Examples

[0092] Performance test of photocatalytic degradation of antibiotics: The experiment of photocatalytic removal of antibiotics in water by the prepared samples was carried out in Beijing Zhongjiao Jinyuan CEL-LAX500 photochemical reactor.

[0093] The test method is as follows: 30 mg of photocatalyst (Cu-CN) is weighed and added to 30 mL of tetracycline hydrochloride aqueous solution (TCH, 40 mg / L); before illumination, the above solution is continuously stirred in a dark environment for 20 min to achieve adsorption-desorption equilibrium between the catalyst and TCH; after adsorption equilibrium, sodium persulfate (PDS) is added to make the concentration of persulfate 2 mmol / L. Subsequently, the light source is turned on, 1.5 mL of solution is taken every 5 min, and 1.5 mL of methanol (quencher) is immediately mixed in, and then the photocatalyst is removed by membrane filtration (0.22 μm), and the TCH concentration in the solution is tested by high performance liquid chromatography; finally, the experimental data is recorded and analyzed, the power is turned off, and the device is cleaned. Among them, the temperature of the photocatalytic experiment is controlled at 25 ° C by a circulating cooling system, and the light source used is a 300W xenon lamp with a 420nm cutoff filter (CEL-LAX500, Beijing Zhongjiao Jinyuan).

[0094] The above method was used to test the performance of Cu-CN photocatalysts in degradation of antibiotics in Comparative Examples 1-3 (basic CN, Cu-CN-0.5-m, Cu-CN-0.5-A) and Examples 1-3 of the present invention. The results are shown in Figure 6 a. Under the same reaction conditions, TCH has basically no obvious degradation when no catalyst is added, indicating that TCH has good stability under visible light. After adding the basic CN obtained in Comparative Example 1, the visible light photocatalytic degradation efficiency of TCH can reach 24% within 30 minutes. After Cu is introduced into CN, the performance of Cu-CN photocatalyst in degrading antibiotics is significantly improved. The efficiency of photocatalytic degradation of TCH by Cu-CN-0.2 photocatalyst is as high as 56%.

[0095] At the same time, we studied the effect of different Cu-EDTA contents on the photocatalytic degradation performance of Cu-CN materials. Figure 6 b. When the Cu-EDTA content is increased during the preparation process, the antibiotic adsorption and degradation rates are greatly improved. The Cu-CN-0.5 catalyst obtained in Example 3 shows the best photocatalytic degradation performance: 98%; however, when the Cu-EDTA content is further increased, the degradation efficiency of photocatalytic degradation of antibiotics decreases. At the same time, we compared the preparation conditions. The degradation rates of TCH by the photocatalytic degradation of the Cu-CN-0.5-m photocatalyst obtained with melamine sponge as a precursor in Comparative Example 2 and the Cu-CN-0.5-A photocatalyst obtained by air calcination in Comparative Example 3 were only 31% and 34%, respectively.

[0096] In addition, we used Cu-CN-0.5 as the catalyst to investigate the stability of the Cu-CN photocatalyst. Figure 7 Under the same photocatalytic reaction conditions, after 5 cycles of reaction, the photocatalytic degradation performance did not decrease significantly, indicating that the Cu-CN photocatalyst prepared by us has excellent cycle stability.

[0097] Experiments have shown that the material described in the present invention is a Cu-CN photocatalyst. The introduction of Cu atoms can broaden the spectral response range and accelerate the transfer and separation of photogenerated electron-hole pairs, effectively improving its photocatalytic activity, and thus has a higher performance in photocatalytic removal of antibiotics.

[0098] In summary, the photocatalyst of the present invention has the advantages of strong light absorption capacity and high photogenerated electron-hole separation efficiency. Experiments have shown that the Cu-CN photocatalyst has a good visible light photocatalytic removal effect on tetracycline hydrochloride, with a removal rate of up to 98% for 40 mg / L tetracycline hydrochloride within 30 minutes, and has excellent cycle stability. The present invention is economical and environmentally friendly, has a simple preparation method, is suitable for industrial large-scale production, and has broad application prospects in environmental governance.

[0099] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

Claims

1. A method for preparing a Cu-modified graphite-phase carbon nitride photocatalyst, characterized in that The method comprises the following steps: Step 1, weighing an appropriate amount of urea and putting it into a ceramic crucible with a cover, calcining it in air, and cooling it to room temperature after calcination to obtain graphite phase carbon nitride (g-C3N4, CN); Step 2, mixing the CN obtained in step 1 with copper ethylenediaminetetraacetate (Cu-EDTA) and methanol, ultrasonicating, stirring, and evaporating in a water bath to obtain a Cu-EDTA / CN mixture; the molar ratio of Cu-EDTA to CN is 0.1 to 2:100; Step 3, placing the Cu-EDTA / CN mixture obtained in step 2 in a covered ceramic crucible and calcining it under the protection of an inert gas, and naturally cooling it to room temperature after the calcination to obtain a Cu-modified graphite phase carbon nitride photocatalyst (Cu-CN).

2. The preparation method according to claim 1, characterized in that: In step 1, the calcination temperature is 550±50°C, the calcination time is 3-6h, and the heating rate is 4-7°C / min.

3. The preparation method according to claim 1, characterized in that: In step 2, the usage ratio of CN to methanol is 0.5-3 mg / mL.

4. The preparation method according to claim 1, characterized in that: In step 2, the ultrasonic time is 10-50 min, the water bath temperature is 55-85° C., and the water bath time is 6-9 h.

5. The preparation method according to claim 1, characterized in that: In step 2, the molar ratio of Cu-EDTA to CN is 0.2 to 2:

100.

6. The preparation method according to claim 1, characterized in that: In step 3, the calcination temperature is 450±50°C, the calcination time is 0.5-2h, and the heating rate is 2-4°C / min.

7. A Cu-modified graphite-phase carbon nitride photocatalyst prepared by the preparation method according to claim 1.

8. Use of the Cu-modified graphite-phase carbon nitride photocatalyst according to claim 7 in photocatalytic degradation of antibiotics.

9. The use according to claim 8, characterized in that The application is: under light, the antibiotics and the Cu-modified graphite phase carbon nitride photocatalyst as a photocatalyst are mixed in a solvent system, the photocatalyst concentration is 0.5-1.5 mg / mL, and the antibiotic concentration is 20-60 mg / L.

10. The use according to claim 9, characterized in that: The lighting conditions were natural light or xenon lamp light source.